Islamic law and modern guarantees in Malaysia - Ab Rahman, Suhaimi (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
The guarantee is regarded as the most common instrument used in the business of commercial banks. Being simplest and least expensive, it is regarded as the most acceptable form of security in the banking lending transactions. However, due to the ‘unfettered discretion’ that the law gives to the creditor banker upon defaults, the reception of the instrument has decreased. This paper seeks to discuss the above issue in the light of Islamic legal point vis-à-vis the current position of Malaysian law of guarantee. The paper suggests that amendments should be made to the existing laws and this could be made through the process of harmonization of Islamic and Malaysian laws.